EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA CAI DENGAN TIPE TUTORIAL TERHADAP HASIL BELAJAR SISWA SMK MUHAMMADIYAH 9 MEDAN - Roni Priyanda (Jurnal Dimensi Matematika, 2019)
The formulation of the problem in this study are: (1) How is the activeness of learning mathematics using the Somatic Auditory Visualization Intellectually (SAVI) model in Modern Muhammadiyah 57 Middle School students on 2017 / 2018? (2) Can learning using the Somatic Auditory Visualization Intellectually (SAVI) model improve learning activeness in Modern Muhammadiyah 57 Middle School students on 2017 / 2018 ?. This researcher aims (1) to find out how active mathematics learning is using the Somatic Auditory Visualization Intellectually (SAVI) model in Muhammadiyah 57 Modern Middle School students on 2017 / 2018. (2) To find out whether learning using the Somatic Auditory Visualization Intellectually (SAVI) model can improve learning activities in Modern Muhammadiyah 57 Middle School students on 2017 / 2018. This type of research is classroom action research. The data of this study were obtained through tests and observations and the subjects in this study were students of class VII-C SMP 57 Modern Muhammadiyah on 2017 / 2018. With 26 students consisting of 17 male students and 9 female students. This research was conducted in two cycles, namely cycle I and cycle II. Each cycle has stages, namely: planning, implementing, observing and reflecting. Student improvement data obtained in the field is written in the form of tables and diagrams. After analyzing the data, several findings were obtained, namely the initial test showed that students completeness reached 15.38% (4 students), cycle I reached 65.38% (17 students) and an increase of 50%, and cycle II reached 88.46% (23 students) and an increase by 73.08%. Thus in cycle II students' classical learning completeness was fulfilled because ≥ 75%. Based on the results of the study, it can be concluded that the use of the Somatic Auditory Visualization Intellectually (SAVI) learning model can increase learning activeness in Modern Muhammadiyah 57 Middle School students on 2017 / 2018.